DISTRIBUTIONAL PATTERNS OF INDIAN SPECIES OF LEMA FABRICIUS (CRIOCERINAE : CHRYSOMELIDAE) - ANAND, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
The family Chrysomelidae is one of the largest families of the Coleoptera and contains about 30,000 known species and is very largely represented in India. The genus Lema Fabricius, on which the present studies are based belong to the subfamily Criocerinae. This subfamily is represented in the Indian fauna mainly by the genus Lema, of which 88 species are known from India alone out of 117 species from Oriental region. Jacoby and Clavareau (1904) reviewed the beetles of the subfamily including characters and the geographical distribution of the species. Jacoby (1908) in the fauna of British India, Vol. I, has given a detailed description of the Indian species along with their distribution. The genus Lema is best recognised by the constriction at sides of thorax and by partly united claws at the base. The other diagnostic characters are head generally constricted posteriorly, antennae filiform, eyes frequently notched, elytra punctate-striate, legs elongate, femora moderately thickened, first ventral segment much longer, prosternum narrow. The species vary greatly in size and colouration but none can be called large.